(ﻣظﺎھر اﻟﺗذﺑذب و اﻟﺗﻐﯾر اﻟﻣﻧﺎﺧﻲ واﻟﻌواﻣل اﻟﻣؤﺛرة ﻓﯾﮫ (ﺑﺣث ﻣﺳﺗل ﻣن أطروﺣﺔ دﻛﺗوراه (Journal of the College of Education for Women, 2019)
Longer fluctuations, climate change and one of the most prominent problems facing the man and his environment to the overall elements and phenomena since ancient times, and today this problem has become one of the most serious current and future challenges facing humanity in view of the cause of these changes from the effects directly in the various aspects of life, environmental and economic man. Since the climate was interested in the problems of rights and activities of all, so a study fluctuations and climatic changes of the important topics which captured the attention of scientists, researchers and specialists in all fields, whether climatic seasons or Hyderologiin or Bailugiyn and other disciplines, and the fact that this problem is no longer an immediate problem extends for one year or a decade, but that the studies and scientific research confirmed it will continue long years and will affect the lives of our children and grandchildren, and because of recent changes in climate that have occurred in recent decades, much different from other environmental problems of overlap at the heart of modern societies. Furthermore, such fluctuations and changes have taken opposite directions has made her something of the inevitable, and where drought, which is spread on the side of the world coincides with the devastating flood and a landslide on the other side, and regions suffering from a sharp decline and a large temperature and the other is on the rise and clear, so the frequency the occurrence of such phenomena in climate and in various parts of the world the effects of attention to these changes that occur from time to time, leading scientists and specialists climate that earned on these fluctuations and changes to climate change Climate change, especially after noticing that the Earth's climate is witnessing a rise in temperature due to human use is rational for a person to environmental and natural resources, causing an imbalance in the global ecosystem as a result of release of greenhouse gases and ozone depletion, which will show the planet to survive the dangers that threaten it .